Comparative osteoradionecrosis rates in bony reconstructions for head and neck malignancy. Issue 9 (September 2019) - Li, Henry; Tan, Meily Dewi Mulyadi; Alexander, Skaria; Grinsell, Damien; Ramakrishnan, Anand
Summary: Background: Bony free flaps are used to reconstruct head and neck cancer defects. The most commonly used flaps are the free fibula flap and the deep circumflex iliac artery (DCIA) flap. Radiotherapy may be given post-operatively to prevent cancer recurrence. This radiotherapy can, however, destroy the bone; a complication termed osteoradionecrosis (ORN). Although there have been studies comparing free fibula and DCIA flaps in terms of success rates and complications, few have assessed the incidence of ORN in both groups. Methods: A retrospective cohort study was conducted involving patients from Royal Melbourne Hospital and St Vincent's Hospital Melbourne who had either a free fibula or DCIA flap for head and neck cancer reconstruction in the past 10 years. Data collected included demographic, operative, and postoperative data. Analysis was performed using Statistical Package for Social Sciences and Microsoft Excel, utilising t-tests, chi-square tests and logistic regression analyses. Results: A total of 154 patients were identified. Of these patients, 127 had free fibula flaps and 27 had free DCIA flaps. Twelve patients had ORN post-op, 10 had free fibula flaps, and 2 had free DCIA flaps. No statistically significant difference was found between the ORN rates in free fibula flaps and free DCIA flaps. Conclusion: Rates of ORN incidence should not be a major consideration in preoperative planning of free flaps for mandibular reconstruction as both fibula and DCIA free flaps are comparable.